Factors Related to Management of non – Asphyxia Low Birth Weight Baby by Midwives in magelang District”s Public Health Centers – 2012 - Tulus Puji Hastuti; Sri Widatiningsih; Mundarti Mundarti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Low birth weight (LBW) is considered as main factor in increasing neonatal and infant morbidity as well as mortality rate, and it has a long term impact on life. Increasing knowledge and skills of health provider is one of strategy to decrease infant mortality rate which can be done by means of training on management of LBW baby and asphyxia. Previous pilot study showed that midwives did not conduct several points on management of non –asphyxia LBW baby. There was 47,7% midwives have had trained on management of LBW baby and asphyxia. This study was aimed to identify relationship between midwives working period, knowledge and motivation towards management of non-asphyxia LBW babies by midwives in Magelang District”s Public Health Centers in 2012. This was an explanatory survey research with cross-sectional approach. Structured quesionaire was used after being tested for its validity and reliability. Independent variables were working period, knowledge and motivation, while dependent variable was execution of non-asphyxia LBW management. There were 46 public health center midwives participated in the research. Stratified random sampling method was applied, sample was drawn from midwives who had been trained on management of LBW and asphyxia. Chi Square “s was applied as analysis method. Majority respondens had a high working period (27 respondens = 58.7%), mostly had a good knowledge (63%), while proportion of midwives who had good and poor motivation was counted the same (50%). There was no relationship between midwives working period, knowledge and motivation towards namagement of non-asphyxia LBW babies as shown by p value of 0.620 (working period), 0.411 (knowledge) and 0.551 (motivation). Multivariate analysis was not conducted because there was no relationship. There was no relationship between midwives working period, knowledge and motivation towards namagement of non-asphyxia LBW babies